Learning to Break the Law: A Criminological Study of Parental Traffic Violations and its Influence on Children’s Behavior in Pakistan - Baloch, Nisar Ahmed Lund; Siyal, Ayaz Hussain; Panhwar, Taha (Annals of Human and Social Sciences, 2025)
This study examines how parental traffic violations in school zones influence children’s future attitudes toward breaking traffic laws. Traffic violations near schools create physical risks for students and normalize illegal behavior. Theoretical frameworks used include Social Bond Theory, Social Learning Theory, and Rational Choice Theory. A mixed-method approach combined direct observations of school zone traffic behavior with structured surveys conducted across schools in Sindh Pakistan. Findings revealed widespread traffic violations by parents, particularly male drivers, including unlawful parking and speeding. Around 78% of surveyed students witnessed their parents violating traffic laws, which strongly correlated with children’s acceptance and imitation of such behavior. Weak police enforcement and peer influence were identified as major contributing factors. Stronger traffic law enforcement around schools, safety education programs for parents and students, and public awareness campaigns are crucial to breaking the cycle of learned illegal behavior and ensuring safer school environments.